Comparative Analysis of Traditional Freshwater Fish Traps Used for Fishing in Ratnagiri, Maharashtra - Aditi R. Banasure; Rahul K. Sadawarte; Balasaheb R. Chavan; Vijay B. Mulye; Jayappa M. Koli; Varsha R. Sadawarte; Swaraj R. Adakney; Mayuresh S. Nagvekar (Journal of Indian Fisheries Association, 2022)
The present study was conducted to document various traditional freshwater fish traps used in Ratnagiri district, Maharashtra. The observations were made from nine blocks of Ratnagiri district where, eight different fishing traps have been reported from eight blocks in different rivers. No traditional freshwater fish trap was reported from Guhagar block of Ratnagiri district. The designs and shape of fish traps were fabricated by local fishermen by using locally available materials namely; Conical trap (Koiny withring), Conical trap(Koiny without ring), Basket trap (Palana), Cylindrical trap (Lutha), Pot trap (Tokya), Metal box trap (Pipe), Plastic container (Dapke) and U-shape trap (Huda). The traditional traps used in Ratnagiri district are seasonal, used in post monsoon. Analysis of variance (ANOVA) showed significant difference (P < 0.05) in length, width, funnel opening and catch rate in these traditional traps. The Cylindrical trap (Lutha) and Conical trap (Koiny withring) showed high catch rate. By using coefficient of determination (r²), trap length showed large effect size (r² = 0.5991). However, width and funnel opening showed small effect of size (R² = 0.0011) and (R² = 0.0007). The study revealed that in this mechanized era the traditional traps are still useful, and there is a need to develop modified traps.